Private Enterprise after the Pandemic A Review of Alternative Scenarios - Yusuf, Shahid (The World Bank, 2021)
The Coronavirus(COVID-19) pandemic has had strong adverse impacts on the private sector in low- and middle-income countries. The future course of the pandemic remains highly uncertain, so consideration of alternative scenarios may be more helpful in assessing investment opportunities and designing policy responses. Based on private sector responses to the pandemic shock, and lessons learned from previous exogeneous shocks, this paper outlines two alternative scenarios for private enterprise during the recovery phase. The scenarios consider a stronger as well as a weaker global economic recovery, and both of these are based on the information available as of end-June 2021. Thus, the scenarios do not discuss developments that have taken place since June 30, which include the emergence of the Delta variant of Coronavirus (COVID-19), and the evolution of vaccine deployment around the world
Keywords: Business Cycles and Stabilization Policies; Business Environment; Economic Growth; Economic Recovery; Investment Climate; Macroeconomics and Economic Growth; Private Sector Development; Private Sector Economics